Intervensi Diet Rendah Garam Pada Pada Pasien Yang Menjalani Hemodialisis: Review Literatur - Siti Yartin; Syahrul Syahrul; Elly L Sjattar (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
Background: Application of low salt diet interventions to reduce health complaints and the risk of heart disease in hemodialysis patients. Method: Search related articles through scientific publications by entering keywords in the PubMed, ScienceDirect, and Google Scholar databases Results: From the 6 articles reviewed, the low salt diet intervention gave changes to systolic and diastolic blood pressure, provided a change in the level of sodium excretion, changes in quality of life and had self efficacy against salt reduction. Conclusion: It is important for nurses, especially hemodialysis nurses, to optimize education regarding the importance of a low-salt diet of less than 2 grams per day through food and beverages consumed, or in the process of preparing and cooking food.